2018
DOI: 10.7150/ijms.23044
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Manifestations and Temporomandibular Disorders of Sjögren Syndrome: An Observational Study

Abstract: AIMS: Sjӧgren Syndrome is a disorder involving oral tissues, with xerostomia, dysgeusia, dysphagia, tooth decay, gingivitis, angular cheilitis and glossitis. Temporomandibular disorders are a generic term referred to clinical conditions involving the jaw muscles and temporomandibular joint. The aim of this study was to investigate the prevalence of oral manifestations and temporomandibular disorders (TMD) in Sjӧgren Syndrome (SS) patients compared with healthy people.METHODS: The study group included 72 SS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…ese results are consistent with accumulating evidence that indicates that subjects suffering from TMD exhibit dysregulation of the systems that control the response of the autonomous and somatomotor systems to sensory stimuli [36]. Furthermore, it has been hypothesized that this dysregulation in TMD patients represents a form of CS [37][38][39][40][41]. In fact, our CSI data indicate that TMD subjects receive high scores, and this is consistent with a role for central involvement that is not observed in control subjects.…”
Section: Discussionsupporting
confidence: 91%
“…ese results are consistent with accumulating evidence that indicates that subjects suffering from TMD exhibit dysregulation of the systems that control the response of the autonomous and somatomotor systems to sensory stimuli [36]. Furthermore, it has been hypothesized that this dysregulation in TMD patients represents a form of CS [37][38][39][40][41]. In fact, our CSI data indicate that TMD subjects receive high scores, and this is consistent with a role for central involvement that is not observed in control subjects.…”
Section: Discussionsupporting
confidence: 91%
“…However, this hypothesis was not validated in this study, and the distribution of the diagnoses of TMD was quite similar in both primary and secondary SS. Crincoli et al (23) also found that signs and symptoms related to TMD were very frequent in a sample composed predominantly of patients with the primary form of the disease.…”
Section: Discussionmentioning
confidence: 95%
“…However, OMD has rarely been described (12), and the signs and symptoms of TMD are not entirely understood in patients with SS (20)(21)(22)(23). Prior studies revealed distinct aspects of primary SS and SS associated with rheumatoid arthritis (RA), and this last group (i.e., secondary SS) is more likely to mimic the classic forms of TMD (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the duration and amount of muscle activity are better predictors of a SB diagnosis than the number of events, and should therefore be used instead of the diagnosis cut-off points used in this study [46]. In addition, subjects were selected based on the criterion "in need of a molar crown", irrespective of their TMD and bruxism status or a TMD-relevant medical history, for example, Sjögren-syndrome [47]. None of the TMD-subjects in this study had relevant diseases in their medical history; nevertheless, it should be kept in mind that the number of participants with an RDC/TMD diagnosis was small, and the results should therefore be interpreted with appropriate caution.…”
Section: Discussionmentioning
confidence: 99%